Supplementary Effect of Different Levels of Nano Zinc Oxide on Zinc Bioavailability and Blood Metabolites in Lambs - Singh, K K; Maity, S B; Maity, A (Indian Journal of Animal Nutrition, 2019)
Twenty five Jalauni male lambs (average body weight = 4.5 kg, age 35 d) were randomly divided into 5 groups of 5 animals each. All the lambs were maintained on basal ration comprising grass hay and concentratemixture (Maize grain, mustard cake and common salt in the ratio of 64: 35: 1). The group G1 served as control supplemented with 40 ppm zinc from ZnO while the lambs in groups G2, G3, G4 and G5 were supplemented with 40, 30, 20, 10 ppm Zn from nano ZnO (nZnO 30 nm) in the concentrate mixture over and above the basal ration(24.12 ppm) for a period of 150 d. Results indicated no difference in the intake and digestibility of nutrients amongst groups. The Zn intake was higher (P